"Does your baby watch TV?": The associations between at‐home TV watching and laboratory challenge cortisol are different for young infants and their mothers. Issue 2 (22nd February 2022) - Thompson, Laura A.; Liberty, Rebecca; Corr, Alora
Abstract: This longitudinal study examined associations between at‐home TV watching and the biological stress response (cortisol) during a laboratory infant cognitive challenge task in 240 3‐ and 5‐month infants and their mothers. Cortisol levels were lower in mothers of 5‐month‐old infants whose infants were exposed to TV at home, compared to mothers of infants that were not TV‐exposed. Cortisol patterns were different across three laboratory sampling intervals for 3‐month‐old infants as a function of TV watching, revealing a sharp increase in laboratory cortisol only for infants who were exposed to TV at home. In contrast, there was no effect of TV exposure in 5‐month‐old infants' cortisol. Infant temperament and demographic measures were included as control variables in regression models to predict maternal and infant cortisol. At 3 months, for the T3 cortisol sampling interval, and at 5 months across all three sampling intervals, maternal cortisol levels were significantly predicted by infant TV exposure after accounting for variance due to these control variables. Our findings show the strong influence of the infant TV‐exposure factor in the biological stress response of mothers of young infants, and suggest that infant TV exposure may influence self‐regulation in 3‐month‐old infants.